3(4-2x)=6(-x+2)

Simple and best practice solution for 3(4-2x)=6(-x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4-2x)=6(-x+2) equation:



3(4-2x)=6(-x+2)
We move all terms to the left:
3(4-2x)-(6(-x+2))=0
We add all the numbers together, and all the variables
3(-2x+4)-(6(-1x+2))=0
We multiply parentheses
-6x-(6(-1x+2))+12=0
We calculate terms in parentheses: -(6(-1x+2)), so:
6(-1x+2)
We multiply parentheses
-6x+12
Back to the equation:
-(-6x+12)
We get rid of parentheses
-6x+6x-12+12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| x-68=-x3 | | 84+(x+58)+(x+11)=180 | | 4a-5=3a-5 | | 70x=-15(x-2) | | 3x-4=2x-2+x | | 3x-8-x=42 | | (2x+12)+x+30=180 | | 4(c+7)=9(c-1)+22 | | 4(x-3)=1/2(x/2+5) | | 5x-2(1/3x-7/3)=22 | | 41/2x+3=3x+12-x | | 90=-4.959+3.496x | | 91=13*n | | h+23=41 | | 2x+13=(3x) | | -26c+52=-390 | | -7+12=9s | | 2x^2-4=x^2+20 | | 2x=3x-5=130 | | w-30=14 | | a+2=5=4a | | 12x-32=32 | | 4.2=-1.4(z-1.5) | | 10s-16=90 | | 5t+83=73 | | 5+p÷2=45 | | 11+6(m-2)=41 | | X^2-6x=6x^2-8x | | 4x+3x-128=322 | | 6n-7=4+7 | | 12=-40.06x+24.58 | | 50q+43-11q+7050q+43=−11q+70 |

Equations solver categories